A genome‐wide association study suggests an association of Chr8p21.3 (GFRA2) with diabetic neuropathic pain. (March 2015) - Meng, W.; Deshmukh, H.A.; van Zuydam, N.R.; Liu, Y.; Donnelly, L.A.; Zhou, K.; ,; ,; Morris, A.D.; Colhoun, H.M.; Palmer, C.N.A.; Smith, B.H.
Abstract: Background: Neuropathic pain, caused by a lesion or a disease affecting the somatosensory system, is one of the most common complications in diabetic patients. The purpose of this study is to identify genetic factors contributing to this type of pain in a general diabetic population. Method: We accessed the Genetics of Diabetes Audit and Research Tayside (GoDARTS) datasets that contain prescription information and monofilament test results for 9439 diabetic patients, among which 6927 diabetic individuals were genotyped by Affymetrix SNP6.0 or Illumina OmniExpress chips. Cases of neuropathic pain were defined as diabetic patients with a prescription history of at least one of five drugs specifically indicated for the treatment of neuropathic pain and in whom monofilament test result was positive for sensory neuropathy in at least one foot. Controls were individuals who did not have a record of receiving any opioid analgesics. Imputation of non‐genotyped SNPs was performed by IMPUTE2, with reference files from 1000 Genomes Phase I datasets. Results: After data cleaning and relevant exclusions, imputed genotypes of 572 diabetic neuropathic pain cases and 2491 diabetic controls were used in the Fisher's exact test. We identified a cluster in the Chr8p21.3, next to GFRA2 with a lowest p ‐value of 1.77 × 10 −7 at rs17428041. The narrow‐sense heritability of this phenotype was 11.00%. Conclusion: This genome‐wide association study on diabetic neuropathic pain suggests new evidence for the involvement of variants near GFRA2 with the disorder, which needs to be verified in an independent cohort and at the molecular level.